Tas Tradisional “Noken” Solusi Mengatasi Limbah Kantong Plastik - Natasya Aulia Husain; Muhamad Yusuf; Akhmad Kadir; Rachmad Surya Muhandy (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
This research tries to completely describe the Mayor of Jayapura's call about the draft regional ordinance on the usage of Noken as an alternative to plastic bags at Jayapura City shopping facilities. It is a qualitative study using the social phenomenology paradigm, involving passive participatory observation, interviews, and documentation. It employs Miles and Huberman's flowchart analysis tools. The Mayor's request for the use of Noken bags in shopping decreases the impact of using plastic bags, which are difficult to degrade with soil in a short period of time. The use of the Noken bag also introduces Papuan culture, which has a straightforward and straightforward philosophy. Rational action in the form of an appeal from the Mayor of Jayapura is looked for, in anticipating the problem of plastic trash that is difficult to degrade by soil and minimizing the accumulation of plastic garbage in rivers in the city of Jayapura, which results in annual flooding. The application of Noken, which sets aims and behaviors through norms, has a philosophical connotation that lies beneath Papuans' common understanding, namely simplicity and transparency. Noken establishes a positive relationship between symbolic arrangements in Papuan society, displaying the forms and patterns of life of the Papuan people, particularly in the city of Jayapura, which reflects the meaning of the simple Papuan people and their openness to others in preserving Papuan culture.